Transcriptome Sequencing Analysis Reveals a Difference in Monoterpene Biosynthesis between Scented Lilium ‘Siberia’ and Unscented Lilium ‘Novano’ - Hu, Zenghui; Tang, Biao; Wu, Qi; Zheng, Jian; Leng, Pingsheng; Zhang, Kezhong (Frontiers in Plant Science, 2017)
Lilium is a world famous fragrant bulb flower with high ornamental and economic values, and significant differences in fragrance are found among different Lilium genotypes. In order to explore the mechanism underlying the different fragrances, the floral scents of Lilium ‘Sibeia’, with a strong fragrance, and Lilium ‘Novano’, with a very faint fragrance, were collected in vivo using a dynamic headspace technique. These scents were identified using automated thermal desorption—gas chromatography/mass spectrometry (ATD-GC/MS) at different flowering stages. We used RNA-Seq technique to determine the petal transcriptome at the full-bloom stage and analyzed differentially expressed genes (DEGs) to investigate the molecular mechanism of floral scent biosynthesis. The results showed that a significantly higher amount of Lilium ‘Siberia’ floral scent was released compared with Lilium ‘Novano’. Moreover, monoterpenes played a dominant role in the floral scent of Lilium ‘Siberia’; therefore, it is believed that the different emissions of monoterpenes mainly contributed to the difference in the floral scent between the two Lilium genotypes. Transcriptome sequencing analysis indicated that ~29.24 Gb of raw data were generated and assembled into 124,233 unigenes, of which 35,749 unigenes were annotated. Through a comparison of gene expression between these two Lilium genotypes, 6,496 DEGs were identified. The genes in the terpenoid backbone biosynthesis pathway showed significantly different expression levels. The gene expressions of 1-deoxy-D-xylulose 5-phosphate synthase (DXS), 1-deoxy-D-xylulose-5-phosphate reductoisomerase (DXR), 4-hydroxy-3-methylbut-2-enyl diphosphate synthase (HDS), 4-hydroxy-3-methylbut-2-enyl diphosphate reductase (HDR), isopentenyl diphosphate isomerase (IDI), and geranyl diphosphate synthase (GPS/GGPS), were upregulated in Lilium ‘Siberia’ compared to Lilium ‘Novano’, and two monoterpene synthase genes, ocimene synthase gene (OCS) and myrcene synthase gene (MYS), were also expressed at higher levels in the tepals of Lilium ‘Siberia’, which was consistent with the monoterpene release amounts. We demonstrated that the high activation levels of the pathways contributed to monoterpene biosynthesis in Lilium ‘Siberia’ resulting in high accumulations and emissions of monoterpenes, which led to the difference in fragrance between these two Lilium genotypes.